2017
DOI: 10.1155/2017/5045973
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Iron Doped Zeolite Imidazolate Framework-8 and Its Remazol Deep Black RGB Dye Adsorption Ability

Abstract: Zeolite imidazole framework-8 (ZIF-8) and the iron doped ZIF-8 (Fe-ZIF-8) were synthesized by the hydrothermal process. The obtained materials were characteristic of X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), scanning electron microscope (SEM), nitrogen adsorption/desorption isotherms, and atomic absorption spectroscopy (AAS). The results showed that the obtained Fe-ZIF-8 possessed the ZIF-8 structure with a large specific area. ZIF-8 and Fe-ZIF-8 were used for the removal of Remazol Deep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…ZIF-8 has pore size between 4–5 Å and possesses a large specific surface area and good water stability as well as it contains abundant acid-base groups. Therefore, it is being used in various fields, especially for the separation of pollutants by adsorption [15,16,17,18,19]. Feng et al [17] studied the adsorption behavior and mechanism between methyl blue (MB) and ZIF-8 in detail.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ZIF-8 has pore size between 4–5 Å and possesses a large specific surface area and good water stability as well as it contains abundant acid-base groups. Therefore, it is being used in various fields, especially for the separation of pollutants by adsorption [15,16,17,18,19]. Feng et al [17] studied the adsorption behavior and mechanism between methyl blue (MB) and ZIF-8 in detail.…”
Section: Introductionmentioning
confidence: 99%
“…Feng et al [17] studied the adsorption behavior and mechanism between methyl blue (MB) and ZIF-8 in detail. Thanh et al [18] reported a one-step synthesis of Fe-ZIF-8 and used it for the removal of Remazol Deep Black RGB dye from aqueous solutions. Zhou et al [19] found that ZIF-8 could simultaneously remove 95.4% Cu and 80.3% norfloxacin.…”
Section: Introductionmentioning
confidence: 99%
“…Various processes for eliminating RBB from aqueous solutions including adsorption, electrochemistry, and biosorption have been reported. Thi Thanh et al [3] reported the efficient removal of RBB using iron-containing zeolite imidazole framework-8 (Fe-ZIF-8). Fe-ZIF-8 possessed high stability.…”
Section: Introductionmentioning
confidence: 99%
“…In order to analyze this electron transfer, the Tanabe-Sugano d 3 diagram was used ( Figure 8) and, according to which, spin-allowed transition was as follows:…”
mentioning
confidence: 99%
“…Zirconium-doped ZIF-8 (Zr/ZIF-8) was synthesized according to a method, which was previously described elsewhere [46,47]. Briefly, 8 mmol of zinc nitrate hexahydrate (Zn(NO 3 ) 2 ·6H 2 O, purity 99.99%) and zirconium (IV) oxynitrate hydrate (ZrO(NO 3 ) 2 ·6H 2 O, purity 99.99%) solutions in a stoichiometric ratio of Zn: Zr = 9:1 were dissolved in 6.2 mmol of methanol.…”
Section: Catalysts Preparationmentioning
confidence: 99%